The Impact Of Strategic Planning On The Performance Of Economic Governmental Organizations: The Moderating Role Of Organizational Leadership And Sustainability - Majed Rashed Mohamed Azair Almansoori; Ali Nasser Ali Al-tahitah; Mohamed Mohamed Kamal Moustafa Battour (Sciences Gates Sdn Bhd, 2024)
Non-Indexed Publication